Multi-Attribute Assessment of Road Design Solutions by Using the Copras Method - Edmundas Kazimieras Zavadskas; Artiras Kaklauskas; Friedel Peldschus; Zenonas Turskis (The Baltic Journal of Road and Bridge Engineering)
Multi-attribute analysis is a popular tool in many economical, managerial, constructional etc problems. The objective of this research is to develop and implement a methodology for multi-attribute assessment of multi-alternative decisions in road construction. After a rough overview of multi-attribute decision support for assessment of road design alternatives, the COPRAS approach was selected. This methodology is applicable to the problems with large numbers of scenarios and criteria. A case study is used to demonstrate the concept of multi-attribute assessment of road design alternatives and the best road design alternative is determined. The research has concluded that the COPRAS method is appropriate for use.